Lactobacillus helveticus SBT2171 Induces A20 Expression via Toll-Like Receptor 2 Signaling and Inhibits the Lipopolysaccharide-Induced Activation of Nuclear Factor-kappa B and Mitogen-Activated Protein Kinases in Peritoneal Macrophages - Kawano, Michio; Miyoshi, Masaya; Miyazaki, Tadaaki (Frontiers in Immunology, 2019)
Lactobacillus helveticus SBT2171 (LH2171) has been reported to ameliorate the development of autoimmune diseases such as collagen-induced arthritis and experimental autoimmune encephalitis in mice and inhibit interleukin (IL)-6 production in antigen-presenting cells in vitro. Regulation of cytokine production by antigen-presenting cells might be critical for the anti-inflammatory function of LH2171 in autoimmune diseases. However, the mechanism and contributing components of LH2171-mediated inhibition of IL-6 production are unclear. Here, we examined the anti-inflammatory effects of LH2171 in lipopolysaccharide (LPS)-stimulated peritoneal macrophages, as a model of antigen-presenting cells, necessary for the pathogenesis of autoimmune diseases. LH2171 significantly reduced LPS-induced expression and secretion of IL-6 and IL-1β cytokines. It also inhibited activation of nuclear factor-kappa B and mitogen-activated protein kinases (NF-κB/MAPKs). Moreover, LH2171 induced gene expression of several negative regulators of NF-κB/MAPKs. Among these regulators, A20 was strongly up-regulated at the mRNA and protein levels upon LH2171 treatment. The cell wall fraction of LH2171 also demonstrated a similar increase in A20 gene expression and exerted an anti-inflammatory effect. These results suggest that the cell wall may be one of the anti-inflammatory components of LH2171. Since cell wall components of Gram-positive bacteria are recognized by toll-like receptor 2 (TLR2), we investigated whether the anti-inflammatory effect of LH2171 was mediated by TLR2 signaling. Specifically, LH2171-mediated IL-6 suppression and A20 upregulation in wild-type macrophages were reversed and significantly reduced in TLR2 knock-out macrophages. These results suggest that LH2171 induces A20 expression via TLR2 signaling, inhibiting the activation of NF-κB/MAPKs and cytokine production in antigen-presenting cells. This might contribute to the anti-inflammatory activity of LH2171 on autoimmune diseases.